Correlating spiritual and emotional intelligence with academic performance among Pakistani students - Turi, Jamshid Ali; Anita, Abdul Rani; Imaduddin, Abidin; Fatimah, Mahmud; Al Adresi, Alaeldeen Saleh (Institute of Advanced Engineering and Science, 2020)
Continuous learning works like a blood for organization and individuals to proceed and succeed. Underdeveloped countries need to address their academic issues. Academic prosperity is linked to economy and technology disruptions so it’s an important element to bring underdeveloped countries up to the mark to thrive and survive in this technical era. Academic prosperity depends upon student’s enthusiastic attitude and their emotional and spiritual intelligences. This study was conducted in learning organizations to see the impact of emotional and spiritual intelligences on academic performance. Population of the study is the academic institutes of Pakistan. Data were collected using cross-sectional questionnaire-based survey from 113 students in Pakistan. The findings provide positive and significant correlations among the types of intelligences and academic performance. Data was analyzed using SPSS and the results were verified using statistical methods like correlation, regression, ANNOVA, Cronbach alpha and means. This study highlights the role of emotional intelligence and spiritual intelligence on academic performance and found out that it has the most demanding and significant effect on the academic performance, therefore it needs better integration in academic practices, routine and culture.